2016
DOI: 10.1080/23744235.2016.1239028
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the costs for the laboratory of flow cytometry screening of urine samples before culture

Abstract: Urine culture samples comprise a large proportion of the workload in clinical microbiology laboratories, and most of the urine samples show no growth or insignificant growth. A flow cytometry-based analyzer (Sysmex Corporation, Japan) has been used to screen out negative urine samples prior to culture in the Päijät-Häme district. We applied decision analytic modelling to analyze, from a laboratory perspective, the economic feasibility of the screening method as compared to culture only (conventional method) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Although studies have shown an economic benefit of the use of urine flow cytometry before urine culture [ 34 ], the impact on the prescription of antibiotics remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have shown an economic benefit of the use of urine flow cytometry before urine culture [ 34 ], the impact on the prescription of antibiotics remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…As suggested by different studies [20, 24, 25], one strategy for establishing cut-off values is to maximize Youden's index. Our results suggest that this strategy does not lead to useful cut-offs in many clinical presentations, as the resulting cut-offs can neither be used to “rule in” (high LR(+)) nor be used to “rule out” (LR(-)) significant bacterial growth in the urine culture but lead to balanced cut-offs with regard to LR(+)/LR(-).…”
Section: Discussionmentioning
confidence: 99%
“…The reliability of this approach is an ongoing subject of discussion [ 3 ]. In recent years, urine flow cytometry (UFC) has been evaluated as a reliable and efficient method to diagnose bacteriuria, revealing heterogeneous results in different patient populations [ 4 , 5 , 6 ]. Patients scheduled for surgery are of particular interest, as asymptomatic bacteriuria is of relevance in urothelium-traumatizing urological procedures [ 1 ].…”
Section: Introductionmentioning
confidence: 99%